Intervensi Konseling Untuk Mengatasi Toxic Parenting - Jimmy Leonardo; Juliana Hindradjat (ATOHEMA: Jurnal Teologi Pastoral Konseling, 2026)
Toxic parenting refers to destructive parenting patterns that negatively affect a child’s development. This harmful parenting style is characterized by behaviors such as excessive control, verbal abuse, emotional neglect, and unrealistic expectations toward children. These conditions can lead to various mental health problems in children, including low self-esteem, anxiety, depression, as well as aggressive or withdrawn behavior. Moreover, toxic parenting often persists across generations if left unaddressed. This article discusses a counseling case study of a family demonstrating toxic parenting practices, along with intervention efforts aimed at improving the parenting dynamics. The method employed is a descriptive qualitative single-case study, with data collected through observation and counseling interviews. The findings indicate that toxic parenting within the family led to emotional and behavioral problems in the child; however, through intensive counseling intervention, improvements were observed in parental communication patterns and behavior. The discussion relates the case findings to relevant literature, affirming that parental awareness and professional assistance can break the cycle of toxic parenting. The conclusion emphasizes the importance of positive parenting education, emotional regulation, and effective communication for parents as preventive measures against toxic parenting, as well as the need for counseling support for families experiencing harmful parenting patterns.